Inter-Regional Disparities with Multi-Dimensional Aspect in India (International Journal of Scientific Research and Management (IJSRM), 2016)
The study explains the disparities with multi-dimensional aspects in India. Some of its major dimensions include: The level of economic growth, level of education, level of health services, status of women, level of nutrition, etc., the disparities almost exist in all aspects which mentioned above numerous measures have undertaken to reduce the disparities but still it wide in India.